2019
DOI: 10.1186/s12885-019-5934-4
|View full text |Cite
|
Sign up to set email alerts
|

Exceptional response to chemotherapy followed by concurrent radiotherapy and immunotherapy in a male with primary retroperitoneal serous Adenocarcinoma: a case report and literature review

Abstract: Background Primary retroperitoneal serous adenocarcinoma (PRSA) is an extremely uncommon malignancy exclusively reported in females. Due to the rarity of the disease, it is difficult to establish a standardized treatment. Case presentation We describe a unique case of PRSA in a 71-year-old male who presented with right-sided lower back pain and numbness. Magnetic resonance imaging identified a mass invading the adjacent psoas muscle and twelfth rib. Tissue biopsy confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…In a case of primary retroperitoneal serous adenocarcinoma, the combination of immunotherapy with radiotherapy decreased the tumor size, and subsequently led to durable disease control. 22 Another research study showed that radiotherapy may improve systemic responses to anti-PD1/PD-L1-directed immune therapy in Merkel cell carcinoma, and immunotherapy clearly showed abscopal regression. 23 Coincidentally, a case report also suggested that immunotherapy increases the chance of an abscopal effect occurring after radiation therapy in a patient with lung adenocarcinoma treated with atezolizumab and subsequently combined with brain irradiation for the treatment of metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…In a case of primary retroperitoneal serous adenocarcinoma, the combination of immunotherapy with radiotherapy decreased the tumor size, and subsequently led to durable disease control. 22 Another research study showed that radiotherapy may improve systemic responses to anti-PD1/PD-L1-directed immune therapy in Merkel cell carcinoma, and immunotherapy clearly showed abscopal regression. 23 Coincidentally, a case report also suggested that immunotherapy increases the chance of an abscopal effect occurring after radiation therapy in a patient with lung adenocarcinoma treated with atezolizumab and subsequently combined with brain irradiation for the treatment of metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…In a case of primary retroperitoneal serous adenocarcinoma, the combination of immunotherapy with radiotherapy decreased the tumor size, and subsequently led to durable disease control. 17 Another research study showed that radiotherapy may improve systemic responses to anti-PD1/PD-L1-directed immune therapy in Merkel cell carcinoma, as well as the immunotherapy has the clarity on abscopal regression. 18 Coincidentally, a case report also suggested that immunotherapy increases the chance of an abscopal effect occurring after radiation therapy in a patient with lung adenocarcinoma treated with atezolizumab and subsequently combined with brain irradiation for the treatment of metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Histological subtypes of retroperitoneal epithelial carcinomas include mucinous [ 8 , 9 , 10 , 11 , 12 , 13 ], serous [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ], endometrioid [ 30 , 31 , 32 , 33 , 34 ], clear cell [ 35 , 36 , 37 , 38 ], and carcinosarcoma [ 39 , 40 , 41 ]. Morphologically, mucinous, serous, and endometrioid tumors resemble the phenotype of the colon, fallopian tube, and endometrium, respectively [ 42 ].…”
Section: Classification Of Retroperitoneal Carcinomasmentioning
confidence: 99%